An Overview of the Treatment Contributions Measured Globally for the COVID-19 Outbreak - Naz, Sheikh S.; Munir, Iqra (Coronaviruses, 2021)
Background: SARS CoV2 is a newly emerged animal beta coronavirus that causes respiratory illness. This infection has affected 212 countries to date and has been declared a pandemic by the World Health Organization. Due to the high transmission rate and lack of availability of any approved anti-viral drug, the formulation of a specific anti-viral therapy has now become a global emergency. Genomic studies have revealed a 79% identity of SARS CoV2 with SARS CoV and 50% identity with MERS CoV, which has given a clue point to test the drugs that were efficient against previously encountered beta coronaviruses. For this purpose, several clinical trials based on the knowledge of existing drugs are moving ahead. These therapies include chloroquine and hydroxychloroquine, remdesivir, corticosteroids therapy, favipiravir, ribavirin, lopinavir/ritonavir, anti-cytokine therapy, and convalescent sera. Aim of the study: The purpose of this review is to give a pointer of contributions conducted globally, including strategies utilized for treatments, the pattern of dosage, adverse reactions, and effective outcomes from different drugs. Methodology: Literature has been retrieved from PubMed, PubMed Central, ResearchGate, ScienceDirect, and Google Scholar, using a combination of keywords for extensive information. Conclusion: Among all the drug options, Remdesivir and the use of Convalescent Sera have been considered as the safest options for treatment against COVID-19. Data from the ongoing clinical trials will be required for the formulation of a specific and approved anti-viral drug.
Keywords: COVID-19 treatments